Investigating the Plant Microremains on Ceramic Li Tripods to Ascertain Their Function and the Plant Resource Exploitation Strategies During the Lower Xiajiadian Culture Period in Chifeng, Northeast China - Liu, Shu; Jia, Xin; Sun, Yonggang; Ma, Zhikun (Frontiers in Earth Science, 2022)
In undertaking a functional study of ceramic Li tripods, a common archaeological artifact in Northeast China during the Bronze Age, this study provides a crucial insight into both the function of these ceramics, plant resource strategies and human diets during this period. The precise function of the Li tripod has to date been controversial due to a lack of direct contextual evidence. Hence, this paper presents analyses of 10 Li tripods from six sites in the Chifeng area of Northeast China, all of which can be dated from their excavation contexts to the Lower Xiajiadian cultural period (3,900–3,400 cal. a B.P.). The interior and exterior surfaces of the tripods were analyzed using starch grain analysis, phytolith analysis and microfossil charcoal analysis. A total of 133 starch grains were recovered, of which 111 (83.46%) were found on 80% of the interior surfaces examined. Further analysis found that these starch grains had damage features specifically gelatinised characteristics, which were consistent with the starch grains that had been boiled in our cooking simulations. In addition, there were obvious soot traces on the surfaces of the tripods, 2,835 microfossil charcoal grains not completely burned were identified, and 70% of the exterior surface samples had a higher frequency of contact with fire. These findings serve to confirm that Li tripods were used in the cooking of food. Of the 133 starch grains found, only 62 could be identified to species level. These were foxtail millet (Setaria italica) and broomcorn millet (Panicum milliaceum) and plants from Triticeae taxa, as well as roots and tubers. The 3,424 phytoliths recovered from the 10 tripods were found to belong to the Panicoideae and Pooideae genera, of which the husks from foxtail and broomcorn millets from the Panicoideae genus accounted for 6.19% of the total. These results indicate that millets, the Triticeae, roots, and tubers, in addition to plants from Panicoideae and Pooideae genera, were utilized in the Chifeng area of Northeast China during the Bronze Age. This study deepens our understanding of the local subsistence patterns and the social context of early Bronze age civilization in the region.